A reliable numerical algorithm for the fractional vibration equation. (October 2017) - Singh, Harendra; Srivastava, H.M.; Kumar, Devendra
Highlights: A reliable algorithm is proposed for the approximate solution of FVE. Solution is also obtained for the cases where the analytical solutions are not known. Error as well as convergence analysis of the proposed method are shown. Numerical results are discussed for different initial conditions and wave velocities. Results are compared with existing analytical methods. Abstract: The key purpose of this article is to introduce a numerical algorithm for the solution of the fractional vibration equation (FVE). The numerical algorithm is based on the applications of the operational matrices of the Legendre scaling functions. The main advantage of the numerical algorithm is that it reduces the FVE into Sylvester form of algebraic equations which significantly simplify the problem. Error as well as convergence analysis of the proposed scheme are shown. Numerical results are discussed taking different initial conditions and wave velocities involved in the problem. Numerical results obtained by using suggested numerical algorithm are compared with the existing analytical methods for the different cases of FVE.